Managing systems migrations and upgrades demystifying the technology puzzle - Breakfield, Charles V.; Burkey, Roxanne E. (Amsterdam ; Boston : Digital Press, 2002)
Managing Systems Migrations and Upgrades is the perfect book for technology managers who want a rational guide to evaluating the business aspects of various possible technical solutions. Enterprises today are in the middle of the R & D race for technology leadership, with providers who increasingly need to create markets for new technologies while shortening development, implementation, and life cycles. The cost for the current tempo of technology life cycles is endless change-management controls, organizational chaos, production use of high-risk beta products, and greater potential for failure of existing systems during migration. Burkey and Breakfield help you answer questions such as, "Is the only solution open to me spending more that the industry average in order to succeed?" and "What are the warning signs that tell me to pass on a particular product offering?" as well as "How can my organization avoid the 'technical death marches' typical of the industry?" This book will take the confusion out of when to make shifts in your systems and help you evaluate the value proposition of these technology changes. Provides a methodology for decision making and implementation of upgrades and migrations Avoids marketing hype and the "technical herding" instinct Offers a tool to optimize technology changes for both staff and customers.
Outside looking in -- Marketplace pulse -- Selling cycle -- Development cycle -- The migration process -- Technology shortfall impact -- Support issues -- Move-forward model.
Includes bibliographical references (p. 433-436) and index.
Keywords: Information technology; Information technology -- Management; Electronic books